Indonesian EFL students anxiety factors and solutions for listening comprehension: Multiple case study - Annisa Astrid; Nyayu Khodijah; Zuhdiyah Zuhdiyah; Ai Yeni Yuliyanti (Universitas Syiah Kuala, 2024)
Students anxiousness affects the EFL listening process. Listening anxiety is also an aspect that may impact a foreign language students success or failure in listening comprehension. Therefore, this study aimed to ascertain the factors that lead to students listening anxiety and the strategies lecturers use to alleviate it. Multiple qualitative case study was the method used in the study. Twenty-one undergraduate students enrolled in a listening class and three lecturers, from three universities in Palembang, Indonesia, participated in this study. Data collection methods included interviews and observation. The results of thematic analysis of qualitative data revealed four factors contributed to students anxiety when listening: 1) lack of listening skills; 2) lack of attention; 3) mood; and 4) classroom environment. Meanwhile, the lecturers were committed to implementing strategies that alleviate students listening anxiety. These strategies included: 1) preparing students for listening activities, 2) exposing them to a variety of authentic listening materials, and 3) improving the learning environment. The research findings imply that the lecturers who taught listening class have observed that each student experienced anxiety while listening due to specific factors. As a result, they have begun to devise suitable teaching strategies to foster a more enjoyable learning experience in listening classes, thereby enhancing student comfort and engagement.